Ultrahigh saturation magnetization microwave composite material and preparation method thereof
By adding carbonyl iron and boric acid to the microwave ferrite material, microwave composite materials with ultra-high saturation magnetization are prepared, which solves the problem that existing materials are difficult to further improve the saturation magnetization, and promotes the miniaturization and high frequency of microwave devices.
Patent Information
- Application Number
- CN202411943032.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-18
AI Technical Summary
Existing microwave ferrite materials are difficult to further improve their ultra-high saturation magnetization, limiting the miniaturization and high frequency of microwave devices.
Ni-based ferrite is used as the matrix, carbonyl iron and boric acid are added, and the composite material is prepared by sintering, ball milling, mixing and sintering, thereby improving its saturation magnetization.
Microwave composite materials with ultra-high saturation magnetization have a maximum saturation magnetization of up to 6250 Gs, which helps to miniaturize and high frequency of microwave devices.
Smart Images

Figure CN119638399A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of microwave ferrite materials, and in particular to an ultra-high saturation magnetization intensity microwave composite material and a preparation method thereof. Background Art
[0002] As microwave devices develop towards small integration, multi-function and high frequency, microwave ferrite, as a key material of microwave devices, has also put forward higher performance requirements. Saturation magnetization is an important parameter of microwave ferrite. Selecting materials with higher saturation magnetization is conducive to improving the gyromagnetic effect, reducing the size of the device, and increasing the operating frequency of the device.
[0003] At present, the research on ultra-high saturation magnetization microwave ferrite mainly focuses on the adjustment of material formula and process. The Ni-based spinel produced by the Southwest Institute of Applied Magnetism has a saturation magnetization of up to 5200 Gs, but it is difficult to further improve its saturation magnetization due to the characteristics of the ferrite material itself and the current process level. Summary of the invention
[0004] One of the purposes of the present invention is to provide a microwave composite material with ultra-high saturation magnetization intensity to solve the above problems.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows: a microwave composite material with ultra-high saturation magnetization intensity, wherein the material is based on Ni-based ferrite, and carbonyl iron and boric acid are added; the content of the carbonyl iron in the composite material is 1-40 wt%, and the content of the boric acid in the composite material is 1-10 wt%. That is, in the composite material, by mass percentage, the carbonyl iron accounts for 1-40 wt%, the boric acid accounts for 1-10 wt%, and the balance is Ni-based ferrite.
[0006] The ferrite matrix used in the present invention is spinel microwave Ni-based ferrite (its composition is generally: 50-55 mol%Fe 2 O 3 , 5~15 mol% ZnO, the balance is NiO, a total of 100%), the saturation magnetization is about 5200 Gs, the carbonyl iron used has the characteristics of high saturation magnetization, and its chemical formula is Fe(CO) 5 ; The composite method of carbonyl iron and Ni-based ferrite effectively improves the saturation magnetization intensity of microwave ferrite; the main function of the auxiliary solvent boric acid is as an auxiliary solvent, and its chemical formula is H 3 BO 3Compared with other co-solvents, boric acid has a low melting point (169°C), which can promote the sintering of the composite material. At the same time, it will not react with ferrite and carbonyl iron in the solid phase, or form a solid solution, which will affect the performance of the composite material. Adding an appropriate amount of boric acid is beneficial to the densification of the composite material, and is beneficial to the saturation magnetization intensity and ferromagnetic resonance line width of the material. However, as a non-magnetic substance, the inventors have found through a large number of experiments that excessive addition will have a negative effect on its magnetic properties, so the amount of boric acid added needs to be controlled within a certain range.
[0007] As a preferred technical solution, the content of the carbonyl iron in the composite material is 5-35 wt%, and the content of the boric acid in the composite material is 2 wt%.
[0008] The second object of the present invention is to provide a method for preparing the above-mentioned ultra-high saturation magnetization intensity microwave composite material, comprising the following steps: (1) Sintering Ni-based ferrite powder at a sintering temperature of 1150°C to 1250°C for 2 to 6 hours; (2) ball milling the Ni-based ferrite powder sintered in step (1) for 15 to 25 hours; (3) weighing the Ni-based ferrite powder after ball milling in step (2), carbonyl iron, and boric acid according to the above ratio, and then mixing them evenly to obtain a composite powder; (4) adding a binder to the composite powder obtained in step (3) to granulate the composite powder, and pressing the composite powder into a green compact at a molding pressure of 100 MPa to 500 MPa to obtain a green compact; (5) Sintering the green body obtained in step (4) at a sintering temperature of 900°C to 1200°C for a holding time of 10 min to 120 min.
[0009] As a preferred technical solution, step (1) is carried out in a bell furnace.
[0010] As a preferred technical solution, the Ni-based ferrite powder D obtained in step (2) 50 2 μm~8 μm.
[0011] As a preferred technical solution, the mixing method in step (3) is ball milling in a drum ball mill, the ball milling time is 2 hours to 6 hours, and the ball milling medium is anhydrous ethanol.
[0012] As a preferred technical solution, the binder in step (4) is a polyvinyl alcohol aqueous solution with a concentration of 5 wt% to 15 wt%.
[0013] As a preferred technical solution, step (5) is sintered in a nitrogen furnace.
[0014] Compared with the prior art, the advantages of the present invention are as follows: the present invention uses metal magnetic powder with high saturation magnetization intensity to compound with ferrite to obtain a microwave composite material with ultra-high saturation magnetization intensity, and its maximum saturation magnetization intensity can reach 6250 Gs, which is beneficial to the miniaturization and high frequency of microwave ferrite devices; the preparation process of the microwave composite material with ultra-high saturation magnetization intensity involved in the present invention is simple, and the traditional ferrite preparation process can meet the requirements, which is conducive to industrial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 is a SEM image of the composite material obtained in Example 1 of the present invention; Figure 2 is a SEM image of the composite material obtained in Example 2 of the present invention; Figure 3 is a SEM image of the composite material obtained in Example 3 of the present invention; Figure 4 This is a SEM image of the composite material obtained in Example 4 of the present invention. DETAILED DESCRIPTION
[0016] The present invention will be further described below in conjunction with embodiments.
[0017] Example 1 A microwave composite material with ultra-high saturation magnetization intensity, which is composed of Ni-based ferrite (saturation magnetization intensity is 5200 Gs±5%, the remaining embodiments and comparative examples below all use this ferrite material) as a matrix, carbonyl iron and boric acid are added, the Ni-based ferrite content is 93 wt%, the carbonyl iron content is 5 wt%, and the boric acid content is 2 wt%; the preparation method thereof comprises the following steps: (1) Sintering Ni-based ferrite powder in a bell furnace at a sintering temperature of 1180°C for 5 hours; (2) The Ni-based ferrite powder obtained in step (1) was ball-milled using a drum ball mill for 15 hours; (3) The Ni-based ferrite powder, carbonyl iron and boric acid obtained in step (2) are weighed in the above proportions, and ball-milled in a drum ball mill to mix them uniformly for 2 hours; (4) adding a binder to the composite powder obtained in step (3) to granulate the composite powder, and pressing the composite powder into a green compact at a molding pressure of 400 MPa; (5) The green body obtained in step (4) was sintered in a nitrogen furnace at a sintering temperature of 900°C for 60 min. The SEM image of the obtained composite material is shown in FIG. Figure 1 As shown in the figure, it can be seen that carbonyl iron is evenly distributed in the composite material and the microstructure of the obtained composite material is uniform.
[0018] Example 2 A microwave composite material with ultra-high saturation magnetization intensity, which is composed of Ni-based ferrite as a matrix, carbonyl iron and boric acid added, wherein the content of Ni-based ferrite is 83 wt%, the content of carbonyl iron is 15 wt%, and the content of boric acid is 2 wt%; and the preparation method thereof comprises the following steps: (1) Sintering Ni-based ferrite powder in a bell furnace at a sintering temperature of 1180°C for 5 hours; (2) The Ni-based ferrite powder obtained in step (1) was ball-milled using a drum ball mill for 15 hours; (3) The Ni-based ferrite powder obtained in step (2), carbonyl iron and boric acid are weighed in the above proportions, and ball-milled in a drum ball mill for 2 hours to mix them uniformly; (4) adding a binder to the composite powder obtained in step (3) to granulate the composite powder, and pressing the composite powder into a green compact at a molding pressure of 400 MPa; (5) The green body obtained in step (4) was sintered in a nitrogen furnace at a sintering temperature of 900°C for 60 min. The SEM image of the obtained composite material is shown in FIG. Figure 2 shown.
[0019] Example 3 A microwave composite material with ultra-high saturation magnetization intensity, which is composed of Ni-based ferrite as a matrix, carbonyl iron and boric acid added, wherein the content of Ni-based ferrite is 73 wt%, the content of carbonyl iron is 25 wt%, and the content of boric acid is 2 wt%; and the preparation method thereof comprises the following steps: (1) Sintering Ni-based ferrite powder in a bell furnace at a sintering temperature of 1180°C for 5 hours; (2) The Ni-based ferrite powder obtained in step (1) was ball-milled using a drum ball mill for 15 hours; (3) The Ni-based ferrite powder obtained in step (2), carbonyl iron and boric acid are weighed in the above proportions, and ball-milled in a drum ball mill for 2 hours to mix them uniformly; (4) adding a binder to the composite powder obtained in step (3) to granulate the composite powder, and pressing the composite powder into a green compact at a molding pressure of 400 MPa; (5) The green body obtained in step (4) was sintered in a nitrogen furnace at a sintering temperature of 900°C for 60 min. The SEM image of the obtained composite material is shown in FIG. Figure 3 As shown, when the carbonyl iron content reaches a certain amount, the carbonyl iron and ferrite can no longer be clearly distinguished in the microstructure of the composite material, indicating that the carbonyl iron and ferrite can be well integrated.
[0020] Example 4 A microwave composite material with ultra-high saturation magnetization intensity, which is composed of Ni-based ferrite as a matrix, carbonyl iron and boric acid added, wherein the content of Ni-based ferrite is 63 wt%, the content of carbonyl iron is 35 wt%, and the content of boric acid is 2 wt%; and the preparation method thereof comprises the following steps: (1) Sintering Ni-based ferrite powder in a bell furnace at a sintering temperature of 1180°C for 5 hours; (2) The Ni-based ferrite powder obtained in step (1) was ball-milled using a drum ball mill for 15 hours; (3) The Ni-based ferrite powder obtained in step (2), carbonyl iron and boric acid are weighed in the above proportions, and ball-milled in a drum ball mill for 2 hours to mix them uniformly; (4) adding a binder to the composite powder obtained in step (3) to granulate the composite powder, and pressing the composite powder into a green compact at a molding pressure of 400 MPa; (5) The green body obtained in step (4) was sintered in a nitrogen furnace at a sintering temperature of 900°C for 60 min. The SEM image of the obtained composite material is shown in FIG. Figure 4 shown.
[0021] Comparative Example 1 A microwave composite material with ultra-high saturation magnetization intensity, which is composed of Ni-based ferrite as a matrix, carbonyl iron and boric acid added, wherein the content of Ni-based ferrite is 97 wt%, the content of carbonyl iron is 1 wt%, and the content of boric acid is 2 wt%; the preparation method thereof comprises the following steps: (1) Sintering Ni-based ferrite powder in a bell furnace at a sintering temperature of 1180°C for 5 hours; (2) The Ni-based ferrite powder obtained in step (1) was ball-milled using a drum ball mill for 15 hours; (3) The Ni-based ferrite powder, carbonyl iron and boric acid obtained in step (2) are weighed in the above proportions, and ball-milled in a drum ball mill to mix them uniformly for 2 hours; (4) adding a binder to the composite powder obtained in step (3) to granulate the composite powder, and pressing the composite powder into a green compact at a molding pressure of 400 MPa; (5) The green body obtained in step (4) was sintered in a nitrogen furnace at a sintering temperature of 900°C for 60 min.
[0022] Comparative Example 2 A microwave composite material with ultra-high saturation magnetization intensity, which is composed of Ni-based ferrite as a matrix, carbonyl iron and boric acid added, wherein the content of Ni-based ferrite is 96 wt%, the content of carbonyl iron is 2 wt%, and the content of boric acid is 2 wt%; the preparation method thereof comprises the following steps: (1) Sintering Ni-based ferrite powder in a bell furnace at a sintering temperature of 1180°C for 5 hours; (2) The Ni-based ferrite powder obtained in step (1) was ball-milled using a drum ball mill for 15 hours; (3) The Ni-based ferrite powder, carbonyl iron and boric acid obtained in step (2) are weighed in the above proportions, and ball-milled in a drum ball mill to mix them uniformly for 2 hours; (4) adding a binder to the composite powder obtained in step (3) to granulate the composite powder, and pressing the composite powder into a green compact at a molding pressure of 400 MPa; (5) The green body obtained in step (4) was sintered in a nitrogen furnace at a sintering temperature of 900°C for 60 min.
[0023] Comparative Example 3 A microwave composite material with ultra-high saturation magnetization intensity, which is composed of Ni-based ferrite as a matrix, carbonyl iron and boric acid added, wherein the content of Ni-based ferrite is 53 wt%, the content of carbonyl iron is 45 wt%, and the content of boric acid is 2 wt%; and the preparation method thereof comprises the following steps: (1) Sintering Ni-based ferrite powder in a bell furnace at a sintering temperature of 1180°C for 5 hours; (2) The Ni-based ferrite powder obtained in step (1) was ball-milled using a drum ball mill for 15 hours; (3) The Ni-based ferrite powder, carbonyl iron and boric acid obtained in step (2) are weighed in the above proportions, and ball-milled in a drum ball mill to mix them uniformly for 2 hours; (4) adding a binder to the composite powder obtained in step (3) to granulate the composite powder, and pressing the composite powder into a green compact at a molding pressure of 400 MPa; (5) The green body obtained in step (4) was sintered in a nitrogen furnace at a sintering temperature of 900°C for 60 min.
[0024] Comparative Example 4 A microwave composite material with ultra-high saturation magnetization intensity, which is composed of Ni-based ferrite as a matrix, carbonyl iron and boric acid added, wherein the content of Ni-based ferrite is 43 wt%, the content of carbonyl iron is 55 wt%, and the content of boric acid is 2 wt%. The preparation method thereof comprises the following steps: (1) Sintering Ni-based ferrite powder in a bell furnace at a sintering temperature of 1180°C for 5 hours; (2) The Ni-based ferrite powder obtained in step (1) was ball-milled using a drum ball mill for 15 hours; (3) The Ni-based ferrite powder, carbonyl iron and boric acid obtained in step (2) are weighed in the above proportions, and ball-milled in a drum ball mill to mix them uniformly for 2 hours; (4) adding a binder to the composite powder obtained in step (3) to granulate the composite powder, and pressing the composite powder into a green compact at a molding pressure of 400 MPa; (5) The green body obtained in step (4) was sintered in a nitrogen furnace at a sintering temperature of 900°C for 60 min.
[0025] Comparative Example 5 A microwave composite material with ultra-high saturation magnetization intensity, which is composed of Ni-based ferrite as a matrix, carbonyl iron and boric acid added, wherein the content of Ni-based ferrite is 85 wt%, the content of carbonyl iron is 15 wt%, and the content of boric acid is 0 wt%; and the preparation method thereof comprises the following steps: (1) Sintering Ni-based ferrite powder in a bell furnace at a sintering temperature of 1180°C for 5 hours; (2) The Ni-based ferrite powder obtained in step (1) was ball-milled using a drum ball mill for 15 hours; (3) The Ni-based ferrite powder, carbonyl iron and boric acid obtained in step (2) are weighed in the above proportions, and ball-milled in a drum ball mill to mix them uniformly for 2 hours; (4) adding a binder to the composite powder obtained in step (3) to granulate the composite powder, and pressing the composite powder into a green compact at a molding pressure of 400 MPa; (5) The green body obtained in step (4) was sintered in a nitrogen furnace at a sintering temperature of 900°C for 60 min.
[0026] Comparative Example 6 A microwave composite material with ultra-high saturation magnetization intensity, which is composed of Ni-based ferrite as a matrix, carbonyl iron and boric acid added, wherein the content of Ni-based ferrite is 77 wt%, the content of carbonyl iron is 15 wt%, and the content of boric acid is 8 wt%; and the preparation method thereof comprises the following steps: (1) Sintering Ni-based ferrite powder in a bell furnace at a sintering temperature of 1180°C for 5 hours; (2) The Ni-based ferrite powder obtained in step (1) was ball-milled using a drum ball mill for 15 hours; (3) The Ni-based ferrite powder, carbonyl iron and boric acid obtained in step (2) are weighed in the above proportions, and ball-milled in a drum ball mill to mix them uniformly for 2 hours; (4) adding a binder to the composite powder obtained in step (3) to granulate the composite powder, and pressing the composite powder into a green compact at a molding pressure of 400 MPa; (5) The green body obtained in step (4) was sintered in a nitrogen furnace at a sintering temperature of 900°C for 60 min.
[0027] Performance Testing: The composite materials prepared in the above embodiments and comparative examples were subjected to relevant tests: the apparent density ρ of the materials was tested by the drainage method. app , use a magnetic ring to measure the specific saturation magnetization σ s , by σ s and ρ app The saturation magnetization intensity is calculated to be 4πM s The ferromagnetic resonance line width ΔH was tested according to GB / T9633-2012, and a scanning electron microscope (TESCAN VEGA3) was used for microscopic morphology analysis. The test results are shown in Table 1.
[0028] Table 1 Properties of different composite materials 4πMs (Guass) ΔH (Oe) <![CDATA[ρ app (g / cm 3 )]]> Example 1 5563 314 5.2302 Example 2 5846 365 5.3231 Example 3 6032 394 5.4315 Example 4 6251 431 5.5133 Comparative Example 1 4863 269 5.0902 Comparative Example 2 4925 275 5.1624 Comparative Example 3 3215 632 5.6123 Comparative Example 4 3156 652 5.6236 Comparative Example 5 5615 463 5.2619 Comparative Example 6 5583 493 5.2426
[0029] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A microwave composite material with ultra-high saturation magnetization intensity, characterized in that: The material is based on Ni-based ferrite, and is further added with carbonyl iron and boric acid. The content of the carbonyl iron in the composite material is 1-40 wt %, and the content of the boric acid in the composite material is 1-10 wt %.
2. The ultra-high saturation magnetization microwave composite material according to claim 1, characterized in that: The content of the carbonyl iron in the composite material is 5-35 wt %, and the content of the boric acid in the composite material is 2 wt %.
3. The method for preparing the ultra-high saturation magnetization microwave composite material according to claim 1 or 2, characterized in that: The steps include: (1) Sintering Ni-based ferrite powder at a sintering temperature of 1150°C to 1250°C for 2 to 6 hours; (2) ball milling the Ni-based ferrite powder sintered in step (1) for 15 to 25 hours; (3) weighing the Ni-based ferrite powder after ball milling in step (2), carbonyl iron, and boric acid according to the above ratio, and then mixing them evenly to obtain a composite powder; (4) adding a binder to the composite powder obtained in step (3) to granulate the composite powder, and pressing the composite powder into a green compact at a molding pressure of 100 MPa to 500 MPa to obtain a green compact; (5) Sintering the green body obtained in step (4) at a sintering temperature of 900° C. to 1200° C. for a holding time of 10 min to 120 min.
4. The preparation method according to claim 3, characterized in that: Step (1) is carried out in a bell furnace.
5. The preparation method according to claim 3, characterized in that: The Ni-based ferrite powder D obtained in step (2) 50 2 μm~8 μm.
6. The preparation method according to claim 3, characterized in that: The mixing method in step (3) is ball milling in a drum ball mill, the ball milling time is 2 hours to 6 hours, and the ball milling medium is anhydrous ethanol.
7. The preparation method according to claim 3, characterized in that: The binder in step (4) is a polyvinyl alcohol aqueous solution with a concentration of 5 wt% to 15 wt%.
8. The preparation method according to claim 3, characterized in that: Step (5) sintering is carried out in a nitrogen furnace.